The rate of adsorption of nanoparticles on microelectrode surfaces - Barnes, E; Compton, R (2013)
Theory is developed for the rate of irreversible adsorption of nanoparticles from solution onto an electrode surface, including the effects of hindered diffusion of large nanoparticles. The effect of nanoparticle size on adsorption processes is studied, and found to be significant for large particles, where the nanoparticle radius to electrode radius ratio is larger than 1 × 10-3. The extent of adsorption in a typical electrochemical nanoparticle experiment at a 5 μm radius hemispherical electrode is studied for different adsorption rate constants, along with the effect this has on concentration of nanoparticles in the vicinity of the electrode and the frequency of impacts of nanoparticles on the electrode. For fast adsorption rate constants, significant and long lasting (in extreme cases greater than 4 h) concentration gradients can form, necessitating careful experimental practice.© 2013 Elsevier B.V. All rights reserved.